The Development of Virtual Reality-Based Electric Motor Rewinding Learning Media for Improving Electrical Equipment Repair Competency in Vocational Schools - Dewi, Ratna; Supriyadi, Edy; Sarwono, Edi (Jurnal Edukasi Elektro, 2025)
This development research aimed to develop, assess the feasibility, determine student responses, and evaluate the effectiveness of virtual reality-based electrical motor rewinding learning media in enhancing electrical equipment repair competency at Vocational High Schools. Using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), the study was conducted at State Vocational High Schools 5 Batam, State Vocational High Schools 7 Batam, and S State Vocational High Schools Teladan Batam. The subjects were 11th-grade students specializing in Electrical Power Installation. Data was collected via interviews, questionnaires, and tests. Expert judgment validated the instruments, and Cronbach Alpha confirmed their reliability. Data analysis involved descriptive statistics and t-tests. The study yielded Virtual Reality based electrical motor re-winding learning media, a guidebook, and job sheets. Feasibility tests showed "very feasible" ratings from both material experts (93%) and media experts (83%). Student responses in the experimental group were "very good" (87%). The media proved effective in improving competency, with experimental group post-test scores significantly higher than the control group. The media demonstrated a "moderate" effectiveness level with a gain score of 0.47, and a t-test value of 0.000 indicated that Ho was rejected and Ha accepted, confirming its effectiveness in enhancing electrical equipment repair competency.